2021
DOI: 10.3390/ijerph18179230
|View full text |Cite
|
Sign up to set email alerts
|

Health and Protective Measures for Seniors during the COVID-19 Pandemic in the Opinion of Polish Society

Abstract: The aim of the study was to determine the opinion of society on the individual care and protection measures towards seniors during the COVID-19 pandemic. In addition, the relationship of opinions with demographic data, knowledge about aging and own experience in contacts with the elderly was examined. The study involved 923 attendees from Poland. The tools used to assess the research problem were: demographic characteristics, a Facts on Aging Quiz (FAQ), the author’s questionnaire about preventive and protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…As it turns out that in retrospect, the social perception of this solution has been mostly negative. A survey performed in February 2021 on a group of 923 respondents indicated that over 50% of people had a negative opinion on the implementation of "senior citizen hours", with women and young people being the majority of those who had a "definitely negative" opinion of the programme (Podhorecka et al, 2021). The Polish Chamber of Commerce also chose to defend the interest of businesses and spoke against this solution.…”
Section: Experience Of the Pandemic And Its Implications For Senior P...mentioning
confidence: 99%
“…As it turns out that in retrospect, the social perception of this solution has been mostly negative. A survey performed in February 2021 on a group of 923 respondents indicated that over 50% of people had a negative opinion on the implementation of "senior citizen hours", with women and young people being the majority of those who had a "definitely negative" opinion of the programme (Podhorecka et al, 2021). The Polish Chamber of Commerce also chose to defend the interest of businesses and spoke against this solution.…”
Section: Experience Of the Pandemic And Its Implications For Senior P...mentioning
confidence: 99%
“…Vergauwen et al [ 31 ] examined a large cross-country dataset (June–July 2020) on older adults’ contact with non-cohabitating children and found that overall contact did not decrease during the pandemic, but rather increased for a large proportion of respondents and decreased only for a minority of respondents. Similarly, Podhorecka et al [ 32 ] found that only a minority of Polish respondents diminished or avoided contact with older people (data collected in February 2021). However, Vergauwen et al [ 31 ] and Podhorecka et al [ 32 ] did not distinguish between direct vs. telephone and online contact in their analysis.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, Podhorecka et al [ 32 ] found that only a minority of Polish respondents diminished or avoided contact with older people (data collected in February 2021). However, Vergauwen et al [ 31 ] and Podhorecka et al [ 32 ] did not distinguish between direct vs. telephone and online contact in their analysis. Instead, Arpino, Pasqualini, and Bordone [ 20 ] distinguished between physical (direct, face-to-face) and non-physical (e.g., video-calls, instant messaging) contact, and analyzed older people’s intergenerational contact during the first lockdown in Italy, Spain, and France (April 2020).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations